2020
DOI: 10.1155/2020/6654063
|View full text |Cite
|
Sign up to set email alerts
|

An Online-Offline Certificateless Signature Scheme for Internet of Health Things

Abstract: The Internet of Health Things (IoHT) is an extended breed of the Internet of Things (IoT), which plays an important role in the remote sharing of data from various physical processes such as patient monitoring, treatment progress, observation, and consultation. The key benefit of the IoHT platform is the ease of time-independent interaction from geographically distant locations by offering preventive or proactive healthcare services at a lower cost. The communication, integration, computation, and interoperabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…According to Xu and Zeng [ 21 ], the propose scheme of Addobea et al [ 20 ] is unable to accomplish correctness, a key security property that should be provided by a signature scheme. In the same year, Khan et al [ 22 ] provided a new COOS solution for IoHT employing hyperelliptic curve discrete logarithm problem hardness (HCDLP). According to Hussain et al [ 23 ], the given approach of Khan et al [ 22 ] is insecure when subject to adaptive chosen message attacks.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Xu and Zeng [ 21 ], the propose scheme of Addobea et al [ 20 ] is unable to accomplish correctness, a key security property that should be provided by a signature scheme. In the same year, Khan et al [ 22 ] provided a new COOS solution for IoHT employing hyperelliptic curve discrete logarithm problem hardness (HCDLP). According to Hussain et al [ 23 ], the given approach of Khan et al [ 22 ] is insecure when subject to adaptive chosen message attacks.…”
Section: Related Workmentioning
confidence: 99%
“…In the same year, Khan et al [ 22 ] provided a new COOS solution for IoHT employing hyperelliptic curve discrete logarithm problem hardness (HCDLP). According to Hussain et al [ 23 ], the given approach of Khan et al [ 22 ] is insecure when subject to adaptive chosen message attacks. It has been proven that an adversary can fake a valid signature on a message by substituting their own public key in place of the one that is supposed to be used.…”
Section: Related Workmentioning
confidence: 99%
“…In signcryption schemes for WBAN, discussed in Table 1, the well-known technique, which is used for the cost efficiency, is bilinear pairing, elliptic curve, and the hyperelliptic curve. According to the experimental results, which is discussed in [21], regarding the major operations, the single pairing operation takes 14.90 milliseconds (ms), single exponential operation takes 1.25 ms, single elliptic scalar multiplication consumes 0.97 ms, and according to [22][23][24][25][26], single hyperelliptic curve needs 0.48 ms, respectively. Thus, from Table 3, we can easily choose the best scheme on the basis of computational cost.…”
Section: Cost Requirements Of Signcryption Technique For Wbanmentioning
confidence: 99%
“…Additionally, we create comparisons among the proposed one and Saeed et al [11], Lu et al [12], Li et al [13], Prameela [14], Omala et al [15], Omala et al [16], Gao et al [17], Ullah et al [18], and Iqbal et al [19] on the basis of milliseconds (ms), which is shown in Table 6. We observed from [21] that the single ESM consumes 0.97 ms, P needs 14.90 ms, PBM consumes 4.31 ms, E needs 1.97 ms, and it is also assumed that HEM earnings consume 0.48 ms [22][23][24][25][26]. Moreover, a computation cost reduction is shown in Table 7 and Figure 5, respectively.…”
Section: Performance Analysismentioning
confidence: 99%
“…The associate editor coordinating the review of this manuscript and approving it for publication was Muhammad Khurram Khan . and others [3]- [7]. IoHT can also be used to track environmental factors such as patient care venues, room status, laboratory shift times, treatment times, and staff-to-patient ratios in addition to medical applications [8]. As a result, this dynamic environment requires a stable yet adaptable connectivity, networking, and computing technology base.…”
Section: Introductionmentioning
confidence: 99%